The Fusion of Javano-Islamic Mysticism in the Story of Dewaruci - Setyawan, Heri (DINIKA : Academic Journal of Islamic Studies, 2018)
Serat Cabolek shows the story which represents the Javanese mysticism, especially as told by the story of Dewaruci. The debate among Haji Amad Mutamakin and Ketip Anom about the spirituality of Dewaruci consist of synthesis Javanese and Islamic mysticism. Particularly, it is the emergence of Hinduism and Islam which shapes Javanese mysticism. Looking carefully at the dialogue and debate between Haji Mutamakin and Ketip Anom about the story of Dewaruci it shows that the concept of Javanese mysticism drawn to the fundamental themes such as what life is what to do in life, and how to live in a good life. Story of Dewaruci shows the significance of batin as an inner essence of a person. The goal of life is seeking water of life that is unity with the Divine. The Divine is not outside there and far from human. The mysticism of Java, therefore, is all about life in the world and human relation with himself, others, and the universe. It is about human activities in all their mundane activities and about human understanding of himself and the universe. Javanese mysticism lays in daily activities. It is in everyday life Javanese coming to the essence of life. These daily activities consist of all relations Javanese made the way of thinking Javanese understood and believed. All aspects become a mystic realm.